1990
DOI: 10.1007/bf00204710
|View full text |Cite
|
Sign up to set email alerts
|

The extent of aspartic acid racemization in dentin: a possible method for a more accurate determination of age at death?

Abstract: Summary. In the current study the objective was to find to what extent a reliable determination of age at death is made possible by establishing the degree of aspartic acid racemization in the dentin of teeth. The results of the investigation of 46 teeth are in agreement with the values found by other authors. The method presented makes a reproducible and accurate estimation of age possible. We intend to elaborate and improve this promising method for determination of age at death. The relevant points are pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 3 publications
3
27
0
1
Order By: Relevance
“…In such cases it is neither possible to obtain coronal dentin nor "entire dentin of central longitudinal sections" in a reproducible manner. Since Yamamoto (1987, 1991) found different values for the extent of aspartic acid racemization in crown and root of the same tooth, the published results for coronal dentin or the "entire dentin of central longitudinal sections" (Helfman and Bada 1976;Ogino et al 1985;Yamamoto 1987, 1991;Ritz et al 1990) cannot be directly applied to root dentin. Ohtani and Yamamoto (1987) investigated exclusively total root dentin in a small number of teeth.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In such cases it is neither possible to obtain coronal dentin nor "entire dentin of central longitudinal sections" in a reproducible manner. Since Yamamoto (1987, 1991) found different values for the extent of aspartic acid racemization in crown and root of the same tooth, the published results for coronal dentin or the "entire dentin of central longitudinal sections" (Helfman and Bada 1976;Ogino et al 1985;Yamamoto 1987, 1991;Ritz et al 1990) cannot be directly applied to root dentin. Ohtani and Yamamoto (1987) investigated exclusively total root dentin in a small number of teeth.…”
Section: Introductionmentioning
confidence: 93%
“…The relationship between age and the extent of aspartic acid racemization in total dentin and the acid soluble and insoluble protein fractions is close enough to serve as a basis for estimation of age at death. A number of studies have shown this method to be more exact and of superior reproducibility than most other techniques for postmortem estimation of age at death (Ogino et al 1985;Yamamoto 1987, 1991;Ritz et al 1990). …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The analytical advantages of dentine were reflected in much improved correlation coefficients over those for enamel. Subsequently, Ogino et al (1985) concluded that age at death determination by aspartic acid racemization in dentine was correct to within ±4 yr. Ritz et al (1990) re-assessed the technique as proposed by Ogino et al (1985) and observed almost identical regression equations relating racemization to age of dentine. Their standard error on the estimate of age at death was somewhat larger at 5.69 yr; however, they concluded that this could be reduced by optimizing the analytical procedure.…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, Ritz et al (1990) concluded that dentine samples would have to be taken from a defined layer to obtain optimum results. • Ohtani et al (2005) measured aspartic acid racemization in the enamel of different teeth from a single individual.…”
Section: Introductionmentioning
confidence: 99%